2015
DOI: 10.1007/s10549-015-3541-x
|View full text |Cite
|
Sign up to set email alerts
|

Supervised physical exercise improves VO2max, quality of life, and health in early stage breast cancer patients: a randomized controlled trial

Abstract: Breast cancer patients suffer impairment in cardiorespiratory fitness after treatment for primary disease, affecting patients' health and survival. The aim of this study was to evaluate the ability of a pragmatic exercise intervention to improve cardiorespiratory fitness of breast cancer patients after primary treatment. Between February 2013 and December 2014, 94 women with early stage (I-III) breast cancer, 1-36 months post-chemotherapy, and radiotherapy were randomly assigned to an intervention program (EX)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 50 publications
0
43
0
1
Order By: Relevance
“…Women with cervical cancer who improved their health behaviors over the 4-month follow-up experienced a two-fold greater improvement in QOL than did those women who made no changes or who increased their risk-prone behaviors (p=0.026). While an intervention study focused on physical activity in breast cancer survivors did result in improved QOL, 29 a meta-analysis of intervention studies designed to improve lifestyle factors for ovarian and endometrial cancer survivors did not show significant improvement in QOL. 30 Further confirmation of the longitudinal effect of changes in health behaviors on QOL in female cancer survivors is needed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Women with cervical cancer who improved their health behaviors over the 4-month follow-up experienced a two-fold greater improvement in QOL than did those women who made no changes or who increased their risk-prone behaviors (p=0.026). While an intervention study focused on physical activity in breast cancer survivors did result in improved QOL, 29 a meta-analysis of intervention studies designed to improve lifestyle factors for ovarian and endometrial cancer survivors did not show significant improvement in QOL. 30 Further confirmation of the longitudinal effect of changes in health behaviors on QOL in female cancer survivors is needed.…”
Section: Discussionmentioning
confidence: 94%
“…4,6 The ability of interventions to improve QOL through health behavior changes is uncertain. Improved QOL following an exercise intervention has been reported in breast cancer survivors, 29 however a meta-analysis including 8 studies of ovarian and endometrial cancer survivors noted only non-significant improvements in QOL following physical activity interventions. 30 …”
Section: Introductionmentioning
confidence: 97%
“…Although the exact mechanisms by which improvements in cardiorespiratory fitness benefits male reproductive potential are not clear yet, several lines of evidence have correlated post-exercise alterations in VO 2max , among others, to improved body composition measures (leanmass:fat-mass) (Casla et al 2015). Therefore, in the present study, post-exercise improvements in semen quality and sperm DNA integrity are likely related, in part, to the effects of exercise training on measures of body composition and cardio-respiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large RCT ( n = 498) reported that combined step aerobic and circuit training modestly reduced bone loss in pre‐menopausal women at the femoral neck (mean BMD difference, 1.2%; 95% CI, 0.2–2.2; P = 0.02). Exercise leads to multiple benefits in women with breast cancer, including improved quality of life, reduced aromatase inhibitor‐associated arthralgia, and possible improved breast cancer outcomes . Evidence regarding vitamin D and calcium supplementation specific to breast cancer survivors is not available.…”
Section: Main Recommendationsmentioning
confidence: 99%